Overview of endovascular thrombectomy accessibility gap for acute ischemic stroke in Asia: A multi-national survey. Issue 5 (July 2020) - Tsang, Anderson Chun On; Yang, I-Hsiao; Orru, Emanuele; Nguyen, Quang-Anh; Pamatmat, Roselyn V; Medhi, Gorky; Wan, Yue; Huang, Song
Endovascular thrombectomy revolutionized the treatment of acute ischemic stroke. Nevertheless, access to endovascular thrombectomy is limited in many parts of the world. Asia holds 60% of the world's population and its countries carry some of the highest stroke disease burden. To understand the availability of endovascular thrombectomy and intravenous thrombolysis in this region, we interviewed stroke neurologists and neuro-interventionists of 19 Asian countries, and found a large disparity in access to endovascular thrombectomy and intravenous thrombolysis between high- and low-income countries. Lack of neuro-interventionists, comprehensive stroke units, stroke triage systems and high treatment cost are the major obstacles to wider accessibility of endovascular thrombectomy, especially among developing countries. The potential solutions to provide equitable access to stroke revascularization therapy are discussed.